2016
DOI: 10.1177/1359105316669582
|View full text |Cite
|
Sign up to set email alerts
|

Look into the crystal ball: Can vivid images of the future enhance physical health?

Abstract: Many impulsive behaviors, unpleasant emotions, and misguided cognitions increase the incidence of type 2 diabetes and other conditions. This study tests the premise that such risk factors are inversely related to future clarity-the extent to which the future seems vivid and certain. Specifically, 211 participants completed the measures of future clarity and various determinants of health. Future clarity was positively associated with the inclination of participants to consume healthy food, abstain from cigaret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…ISSN: 1945-7774 CC by-NC 4.0 2020 Financial Therapy Association 57 Previous research has verified the association between future clarity and responsible behavior (e.g., Wilson, Moss, & Irons, 2017). When individuals perceive their future as vivid and certain, they are more likely, for example, to eat healthy food and abstain from cigarettes (Moss, Skinner, et al, 2018). Indeed, future clarity has been shown to be associated with behaviors that affect finances in impending retirees (Moss, Ghafoori, & Smith, 2018).…”
Section: Limitations Of Previous Research and Aim Of The Present Studymentioning
confidence: 97%
See 1 more Smart Citation
“…ISSN: 1945-7774 CC by-NC 4.0 2020 Financial Therapy Association 57 Previous research has verified the association between future clarity and responsible behavior (e.g., Wilson, Moss, & Irons, 2017). When individuals perceive their future as vivid and certain, they are more likely, for example, to eat healthy food and abstain from cigarettes (Moss, Skinner, et al, 2018). Indeed, future clarity has been shown to be associated with behaviors that affect finances in impending retirees (Moss, Ghafoori, & Smith, 2018).…”
Section: Limitations Of Previous Research and Aim Of The Present Studymentioning
confidence: 97%
“…To illustrate, some people feel their future seems vivid and certain, called future clarity (McElwee & Haugh, 2010). They can imagine their future in some detail (McElwee & Haugh, 2010;Moss, Skinner, Alexi, & Wilson, 2018). As Amit, Algom, and Trope (2009) showed, a future that seems vivid-replete with sensory and emotional details-feels closer in time.…”
Section: Clarity Of the Futurementioning
confidence: 99%
“…In our review of the literature, we found 12 articles in which researchers measured vividness of the future. In the majority of the studies, researchers used self-report measures to assess clarity or vividness of images of the future self [8,51]. In contrast, two studies used a qualitative approach, coding vividness from participants' brief descriptions of their future [18,41].…”
Section: The Vividness Component: Clarity and Ease Of Imagining The Fmentioning
confidence: 99%
“…Researchers studying vividness have used several labels for this component including "vivid mental imagery" [7], "episodic future thinking" [94], "future clarity" [51], and "vividness of the future self" [4]. Although these programs of research use diverse labels, their primary focus is on measuring the clarity of mental images of the future self.…”
Section: The Vividness Component: Clarity and Ease Of Imagining The Fmentioning
confidence: 99%
See 1 more Smart Citation